Potential Therapeutic Applications of MnSODs and SOD‐Mimetics. Issue 20 (12th December 2017) - Bonetta, Rosalin
Abstract: Natural as well as synthetic antioxidants are constantly being investigated for their efficiency in combatting the effects of oxidative stress, which appears to be the responsible cause of several diseases, including cancer, central nervous system disorders, ischaemia‐reperfusion disorders, cardiovascular conditions, and diabetes. Superoxide dismutases (SODs) constitute the ubiquitous antioxidant defences against oxidative stress that underlies numerous pathological conditions. Therefore, the development of therapeutics aimed at either delivering MnSOD more effectively to target tissues in the body in the form of MnSOD gene therapy, or the synthesis of molecules that mimic the activity of superoxide dismutase is constantly being explored. Classes that have been developed as SOD mimetics include the Mn‐metalloporphyrins, Mn‐cyclic polyamines, Mn‐salen complexes, MnPLED derivatives as well as the nitroxides. Thus far, SOD mimetics have shown remarkable efficacy in several animal models suffering from oxidative stress injuries. A promising approach for the future of SOD and SOD mimic therapeutics appears to involve combination treatment of the antioxidants with radiotherapy or chemotherapy. Abstract : Mimicking SOD : Methods that use native MnSODs or molecules that mimic the activity of SOD to treat oxidative stress injuries are in constant development.